Multiple Lactating Adenomas; A Case Report of a Rare Breast Tumour - Nori, Wassan; Ahmed Fareed, Sahar (Scripta Medica, 2025)
A lactating adenoma (LA) is a rare benign breast tumour typically seen during pregnancy and lactation. It is usually presented as a single firm breast mass. Due to LA clinical and imaging features, they can mimic malignant breast cancer and this challenge is further compounded by limited physicians' awareness of LA criteria, leading to diagnostic dilemmas. A case of 19-year-old primigravidae with multiple palpable breast masses, an uncommon presentation of LA is presented. Imaging studies raised malignancy suspicion while core biopsy confirmed the diagnosis of LA. Integration of medical history and histopathology helped establish the case and avoid unnecessary interventions.